Incidence of pressure ulcer and its risk factors in patients at orthopedic wards - Bolourchifard, F; Abdolrahimi, M; Yaghmaei, F; Akbarzadeh Baghban, A. R. (Advances in Nursing & Midwifery, 2010)
Background and aim Pressure ulcer and its related factors are associated with such complications as decreased quality of life of patients and increased cost of health system as important issues of nursing care. This descriptive study was conducted to determine the incidence of pressure ulcer and its related factors in patients at orthopedic wards in 2009. Materials and methods 330 patients with no pressure ulcer at the time of admission, no movement due to therapeutic interventions or movement only with assisting devices were selected through convenience sampling at orthopedic wards of hospitals affiliated to Shahid Beheshti University of Medical Sciences. A demographic questionnaire, “National Pressure Ulcer Advisory Panel“ grading scales and “Braden Pressure Ulcer Assessment Scale” were used for data collection. The tools were validated by content method and inter-rater reliability method was used for the grading system and Braden Scale. Data were analyzed by SPSS 15. Findings 46 patients (%13.9) developed pressure ulcer of which %76.1, %21.7 and %2.2 were at stages 1, 2 and 3 respectively. The most common locations of the ulcers were in sacrum (%34), ischium (%34.8), heels (%17.4) and both sacrum as well as heels (%10.9). The related factors included medical diagnosis, type of therapy, decreased activity and immobility. Conclusion The incidence of pressure ulcers in Tehran is similar to other reports around the world. Risk factors in this regard are old age, lengthy hospitalization, medical diagnosis, type of therapy, decreased activity and immobility. Keywords: Pressure ulcer, Risk factors, Braden Scale. *Corresponding Author: Lecturer, Dept. of Medical-Surgical Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences. Tehran, Iran. E-mail: bolourchi@sbmu.ac.ir